64.9k views
3 votes
Explain 2 ways to evaluate 36(16-26)

User Neil Smith
by
6.6k points

1 Answer

1 vote

We can evaluete the expression: 36 ( 16 - 26) by:

1) Using the Oredr of perations for algebraic expressions, and solving for the values inside the parenthesis first:

so we do: 16 - 26 = -10 first, and then proceed to multiply:

36 (-10) = - 360

2) by usnig Distributive property and therefore multilying the factor 36 which is outside the parenthesis by 16 first, and then by -26 and combining these two results:

36 ( 16 - 26) = 36 * 16 - 36 * 26 = 676 - 936 = - 360

User Nzc
by
6.1k points